Investigation of some acute phase proteins, cytokines and hepcidin values in feline enteric corona virus antibodies and feline infectious peritonitis antigen positive cats - Şahinduran, Ş; Albay, MK; Karaca, M; Karakurum, MÇ; Kiyici, R (Journal of the Hellenic Veterinary Medical Society, 2023)
Feline Infectious Peritonitis (FIP) is a fatal disease caused by feline coronaviruses. The causative agent is Feline Infectious Peritonitis Virus, a mutation of Feline Enteric Coronavirus. Feline Corona Virus is very common in the cat population. In Feline Corona Virus infected cats, the development of FIP depends on the cat’s immune response. FIP disease is more common in young and old cats because young and old animals have a weaker immune system. The acute phase response is a complex systemic reaction that occurs as a response to acute or chronic inflammatory processes such as infection, neoplasia or immunological disorders, tissue damage, trauma and surgery. The study material included 15 cat with presumptive FIP (study group) and 10 healthy cats (control group). Of the 15 cats, 9 (60%) showed dry and 6 (40%) effusive form. Serum amyloid A (SAA), haptoglobin (Hp), α1-acid glycoprotein (AGP), albumin, interleukin-6 (IL-6), hepcidin, alanine-amino transferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), blood urea nitrogen(BUN), and creatinine levels were measured in the serum collected from both groups. There were no difference between the wet and dry FIP in albumin values; haptoglobin, α1-acid glycoprotein, SAA and hepcidin values were significantly different between the two groups. IL-6, showed significant difference in both wet and dry FIP groups. It was also concluded that hepcidin may be used as a biomarker in Feline Infectious Peritonitis disease like other acute phase proteins.